Pharmacological Inhibition of Amyloidogenic APP Processing and Knock-Down of APP in Primary Human Macrophages Impairs the Secretion of Cytokines - Spitzer, Philipp; Walter, Matthias; Göth, Caroline; Oberstein, Timo Jan; Linning, Philipp; Knölker, Hans-Joachim; Kornhuber, Johannes; Maler, Juan Manuel (Frontiers in Immunology, 2020)
It has been previously shown that the amyloid precursor protein (APP) support the innate immune defense as an immune receptor. Amyloid β (Aβ) peptidesseem to have properties of an antimicrobial peptide and an act as opsonines. In APP-deficient mouse models, a reduced secretion of cytokines has been observed. Still, it is unclear whether this can be attributed to the lack of APP or to the missing secretion of Aβ peptides. We inhibited the secretion of Aβ peptides in primary human monocyte derived macrophages with the -secretase inhibitor N-[N-(3,5-Difluorophenacetyl)-L-alanyl]-S-phenylglycine-t-butyl-ester (DAPT) or the β-secretase inhibitor GL-189. Alternatively, we knocked down APP by transfection with siRNA. We measured tumor necrosis factor α (TNFα), interleukin 6 (IL-6) and interleukin (IL-10) by enzyme linked immunosorbent assay (ELISA) and evaluated the phagocytotic activity by flow cytometry. We observed reduced concentrations of TNFα and IL-6 in the media of APPk/d macrophages and after inhibition of the β-, or -secretase, especially after additional immunological activation with lipopolysaccharide (LPS). Secretion of IL-10 was increased after pharmacological inhibition of APP processing when the macrophages were not immunologically activated but was decreased during LPS-induced inflammation in APPk/d macrophages. No changes of the phagocytotic activity were observed. We conclude that macrophage APP and Aβ peptides support the initiation of an immune response and are involved in the regulation of TNFα, IL-6 and IL-10 secretion by human monocyte-derived macrophages.